Printed sustainable elastomeric conductor for soft electronics - Lv, Jian (2024)
The widespread adoption of renewable and sustainable elastomers in stretchable electronics has been impeded by challenges in their fabrication and lacklustre performance. Here, we realize a printed sustainable stretchable conductor with superior electrical performance by synthesizing sustainable and recyclable vegetable oil polyurethane (VegPU) elastomeric binder and developing a solution sintering method for their composites with Ag flakes. The binder impedes the propagation of cracks through its porous network, while the solution sintering reaction reduces the resistance increment upon stretching, resulting in high stretchability (350%), superior conductivity (12833 S cm-1), and low hysteresis (0.333) after 100% cyclic stretching. The sustainable conductor was used to print durable and stretchable impedance sensors for non-obstructive detection of fruit maturity in food sensing technology. The combination of sustainable materials and strategies for realizing high-performance stretchable conductors provides a roadmap for the development of sustainable stretchable electronics.